1999
DOI: 10.1016/s0029-7844(98)00400-1
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of antenatal steroids in obstetric subgroups

Abstract: The effectiveness of antenatal steroids varies with the obstetric population studied. Antenatal steroids significantly decreased the incidence of major neonatal morbidity and mortality in the AGA preterm neonate delivered after preterm labor with intact membranes. Antenatal steroids did not show any benefit in cases of pregnancy associated with maternal hypertension or FGR. Its effect in the presence of PROM is limited to a significant reduction in the incidence and severity of intraventricular hemorrhage and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(32 citation statements)
references
References 16 publications
3
29
0
Order By: Relevance
“…In this study, there was no reduction in necrotising enterocolitis or increase in neonatal culture positive sepsis. This is in agreement with Abbasi et al (2000), Thorp et al (2001) and Elimian et al (1999) and in contrast to other studies (Leviton et al 1993;Vermillion et al 1999;Wright et al 1995a). …”
Section: Commentsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, there was no reduction in necrotising enterocolitis or increase in neonatal culture positive sepsis. This is in agreement with Abbasi et al (2000), Thorp et al (2001) and Elimian et al (1999) and in contrast to other studies (Leviton et al 1993;Vermillion et al 1999;Wright et al 1995a). …”
Section: Commentsupporting
confidence: 93%
“…The TRH study showed an impairment of fetal growth but no effect on head circumference (Banks et al 1999), while Abbasi et al (2000) showed a reduction in head circumference and no effect on birth weight. However, Elimian et al (1999) showed no disturbance in growth with multiple AC. In this study, single AC decreased the risk of total intraventricular haemorrhage when compared with both none and multiple AC.…”
Section: Commentmentioning
confidence: 86%
“…17 Similar results were found in another study of 220 SGA infants weighing ≤1750 g that examined only in-hospital morbidities without examining whether baseline differences in GA existed between the two groups. 18 The same study, however, found improved in-hospital outcomes among appropriate for gestational age infants exposed to ANS compared to those not exposed. 18 In a recent study of singletons and multiples born at 22 to 25 weeks using data from the NICHD NRN, Carlo et al showed that exposure to ANS compared with no exposure was associated with a lower rate of NDI or death among non-SGA infants only; no significant results were seen among SGA infants.…”
Section: Discussionmentioning
confidence: 91%
“…12,17 Growth restriction is not characteristic of all newborn infants exhibiting RDS, and there is conflicting clinical evidence on the extent to which fetal growth restriction increases the risk of neonatal RDS in humans. 4447 The growth restriction phenotype in Erk3 −/− pups may have an impact on the molecular mechanisms of lung maturation that were detected in this study, potentially limiting its applicability to the subset of neonates with RDS who also experienced IUGR. Another possible limitation is in the incomplete comparison of temporal gene regulation and glucocorticoid response between our murine model and previable human fetal tissue not exposed to steroids.…”
Section: Commentmentioning
confidence: 99%